Racialized Citizenship in Superdiverse Europe - Hellgren, Zenia; Bereményi, Bálint Ábel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This volume enquires about how racialization shapes European societies and the lives of people affected by it in myriad ways. It provides a powerful collection of new publications by scholars who, through their research, contribute to placing race and racialization studies at the forefront of European academia.